1980
DOI: 10.1002/sapm1980632147
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Nonbreaking Waves in Hyperelastic Materials

Abstract: This note treats the evolution of waves on hyperelastic materials, due to initial jump discontinuities in the gradient of strain. In general, these discontinuities become unbounded in finite time, leading to discontinuous strain. There are, however, certain cases in which the gradient jump remains finite for all times. We show here that the class of materials admitting such exceptional waves is fairly large, including Hadamard materials and generalized Hooke materials. An earlier example of Jeffrey and Teymur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Earlier, the same material model was used in numerical studies of azimuthal shear (see [16] and [17]), anti-plane shear [35], combined torsion and anti-plane shear [36] and finite torsion [32]. Lustman [34] showed that from all possible forms of the function h(J) in the Hadamard material (8) its Levinson-Burgess form (29) is the only one for which all the generated waves (possibly three-dimensional) are non-breaking waves, i.e. for initial data with weak discontinuities (jumps in the n th or higher order derivatives for n th order equations) lower-order derivatives (and therefore the strain) do not become discontinuous.…”
Section: The Levinson-burgess Materialsmentioning
confidence: 99%
“…Earlier, the same material model was used in numerical studies of azimuthal shear (see [16] and [17]), anti-plane shear [35], combined torsion and anti-plane shear [36] and finite torsion [32]. Lustman [34] showed that from all possible forms of the function h(J) in the Hadamard material (8) its Levinson-Burgess form (29) is the only one for which all the generated waves (possibly three-dimensional) are non-breaking waves, i.e. for initial data with weak discontinuities (jumps in the n th or higher order derivatives for n th order equations) lower-order derivatives (and therefore the strain) do not become discontinuous.…”
Section: The Levinson-burgess Materialsmentioning
confidence: 99%